Performance Simulation Analysis for Magnetorheological Damper with Internal Meandering Flow Valve - Ahmad Zaifazlin, Zainordin; Priyandoko, Gigih; Zamri, Mohamed (Universiti Malaysia Pahang, 2018)
Magnetorheological (MR) damper as a semi-activesystem for a vehiclesuspension is simulatedin this study. The proposed design of Magnetorheological (MR) valve consists of meandering flow channel or gaps that fixedin the piston of the damper. The focus of this study is to estimate the performance of proposed MR valve based on actual front suspension parameter of a vehicle. Annular and radial gaps are combined to produce an MR valve with meandering fluid flow path. Furthermore, the damper is filled with Magnetorheological (MR) fluid to energize the damper under the presenceof magnetic fields.The magnetic flux density within each gap is obtainedvia the Finite Element MethodMagnetics(FEMM)software. Therefore, the yield stress of MR fluid and magnetic flux relationships bothcan be predicted. The presentpaper shows a reduction in pressure dropwhenthe thickness of each gap is increased. Pressure drop is closely affected by the fluid flow rate thatenterseach gap. Thismeans thatthe lowerflow rate increases the pressure drop of MR valve at various current